Implementasi Pembelajaran Biologi Berbasis Bioteistik Studi Fenomenologi di MA YPI Cikoneng Kabupaten Bandung - Linda, Linda Meliawati; Irawan; Rohmat Mulayana (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
The integration of science and religious values in madrasah education often remains dichotomous and lacks deep epistemological unity. This study aims to describe the implementation of Biotheistic-based Biology learning and to reveal the essence of students' spiritual experiences at MA YPI Cikoneng, Bandung Regency. This research employed a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, participatory observation, and documentation studies involving 10 purposively selected key participants. The results indicate that: (1) The implementation of Biotheistic learning is structured through the 'Webbed-Theistic' planning model and the execution of 'Scientific-Spiritual Inquiry,' integrating qauliyah and kauniyah verses; (2) Phenomenologically, students experience a paradigm shift where biological phenomena are viewed not merely as material mechanisms but as theophanies (manifestations) of God's greatness; (3) The essence of students' spiritual experience evolves from cognitive understanding to a sense of awe, culminating in a consciousness of servitude (being). This study concludes that the Biotheistic approach effectively transforms Biology learning into a means of ma'rifatullah (knowing God) that enhances students' spiritual awareness, despite constraints regarding time allocation.